A single-beam spoof surface plasmon polariton leaky-wave antenna with backfire radiation and wide-angle scanning capability - Jinhong Wang; Xiaoming Qi; Guoteng An; Boyu Liu; Binfeng Yang; Yannan Jiang; Longfang Ye (Materials & Design)
A single-beam spoof surface plasmon polariton (SSPP) leaky-wave antenna (LWA) with backfire radiation and wide-angle scanning capability is proposed. In the antenna structure, a Goubau line (GL) with a periodic open ring array etching is specifically designed to support single-mode SSPP transmission. Two flaring grounds with different curvatures and the GL with tapered open rings are utilized to ensure the impedance and mode matching between the quasi-TEM and SSPP modes. To convert the slow-wave SSPP mode into a good single-beam radiation mode, periodic perturbations composed of a two-semi-elliptical patch array and a rectangular reflector are placed on both sides of the SSPP GL. The simulated and measured results validate the effectiveness of the proposed antenna design, particularly demonstrating excellent single-beam radiation performance with backfire and wide-angle scanning. The fabricated SSPP LWA prototype demonstrates a wide single-beam scanning range of 118° between −90° and 28°, an average efficiency of 94.5 %, and an average realized gain of 11.8 dBi in the frequency range of 8.1 – 12.6 GHz. These findings indicate that the proposed LWA holds significant potential applications in radar, microwave imaging, and wireless communication.